Efeito de cimentos endodônticos na resistência adesiva de pinos de fibra e no grau de conversão de dois cimentos resinosos - Bohrer, Thaís Camponogara (2017)
Restoring dental function after partial loss of the coronary structure depends mainly of post retainer adhesive strength. However, several factors may affect the adhesion between the root dentin and the radicular post used including the endodontic sealers used for root canal obturation during endodontic treatment. Therefore, the objective of this study is to evaluate the effect of two endodontic sealers on push-out bond strength between fibreglass posts and root canal wall after different storage times and verify the influence of the endodontic sealers on the degree of conversion of resin cements. For this study, 180 bovine teeth were endodontically treated using two endodontic sealers, eugenol-based (Endofill) or epoxy resin-based (AH Plus). Subsequently, the specimens were stored in 100% relative humidity at 37 °C for 24 h, 6 or 12 months. After the respective storages times, the root canals were prepared for fibreglass post cementation using two resins cements, RelyX U200 or Multilink Automix. The push-out test and the analysis of failures were performed. For the degree of conversion analysis with a Raman microscope. The samples were prepared using only resin cement or resin cement and endodontic sealer. Finally, the push-out data were subjected to statistical analysis and the percentages of degree of conversion were calculated. The AH Plus sealer obtained the highest values of push out bond strength at 24 h and 6 months. There was no difference between the values of AH Plus and Endofill sealer at time 1 year (p < 0.05). Moreover, the degree of conversion was affected by the endodontic sealers used. Therefore, the use of eugenol-based sealer is not recommended because it affects the push-out strength of fibreglass posts.